Pragmatic guide to business process modelling - "Holt, Jon" (UK, 2007)
"Introduction : the magic of processes, background, some basic definitions, risk, the process - The UML diagrams : introduction, modeling, the UML, the class diagram, the activity diagram, the sequence diagram, the use case diagram, consistency between the diagrams - Requirements for process modeling : introduction, specific process modeling requirements, meeting the requirements through modeling, tailoring processes, the process meta-model - The process meta-model expanded : introduction, process concept view, process realization view, the seven views of the meta-model, consistency between views, using the meta-model, extending the process meta-model - Process mapping and metrics : introduction, a process for process mapping, process mapping metrics, application of metrics, interpreting the results - Case study : introduction, background, the approach, interpreting the process model, thcase study process model, process mapping."
includes index
Keywords: Production management; Reengineering (Management)